Cerebral Microdialysis for Protein Biomarker Monitoring in the Neurointensive Care Setting – A Technical Approach - Hillered, Lars; Dahlin, Andreas P.; Clausen, Fredrik; Chu, Jiangtao; Bergquist, Jonas; Hjort, Klas; Enblad, Per; Lewén, Anders (Frontiers in Neurology, 2014)
Cerebral microdialysis (MD) was introduced as a neurochemical monitoring tool in the early 1990s and is currently well established for the sampling of low molecular weight biomarkers of energy metabolic perturbation and cellular distress in the neurointensive care (NIC) setting. There is now a growing interest in MD for intracerebral sampling of protein biomarkers of secondary injury mechanisms in acute traumatic and neurovascular brain injury in the NIC community. The initial enthusiasm over the opportunity to sample protein biomarkers with high molecular weight cut-off (MWCO) MD catheters has dampened somewhat with the emerging realization of inherent problems with this methodology including protein adhesion, protein-protein interaction and biofouling, leading to unstable MD catheter performance (i.e. fluid recovery and extraction efficiency). This review will focus on the results of a multidisciplinary collaborative effort, within the Uppsala Berzelii Centre for Neurodiagnostics during the past several years, to study the features of the complex process of high MWCO MD for protein biomarkers. This research has led to new methodology showing robust in vivo performance with optimized fluid recovery and improved extraction efficiency, allowing for more accurate biomarker monitoring. In combination with evolving analytical methodology allowing for multiplex biomarker analysis in ultra-small MD samples a new opportunity opens up for high-resolution temporal mapping of secondary injury cascades, such as neuroinflammation and other cell injury reactions directly in the injured human brain. Such data may provide an important basis for improved characterization of complex injuries, e.g. traumatic and neurovascular brain injury, and help in defining targets and treatment windows for neuroprotective drug development